A cyan nitrogen oxide fluorescent material that can be excited by purple light and a preparation method thereof

By using the cyan nitrogen oxide fluorescent material of Ba2-xEuxY4SiO7N2, and using Eu2+ activator to emit cyan light under the excitation of purple light, the problem of cyan cavity in the white LED spectrum in the prior art is solved, efficient and stable cyan luminescence, and the color rendering index is improved, which is suitable for high-display LEDs.

CN117586772BActive Publication Date: 2025-04-22XIAMEN UNIV
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202311557725.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-21
Publication Date
2025-04-22
Estimated Expiration
2043-11-21

AI Technical Summary

Technical Problem

The prior art lacks high-performance fluorescent materials that can be excited by purple light and emit cyan light, resulting in the presence of cyan cavity in the white LED spectrum and the color rendering index is low.

Method used

A cyan nitrogen oxide fluorescent material with the general chemical formula of Ba2-xEuxY4SiO7N2 is used. This material uses Eu2+ as the activator. Under the excitation of purple light, the main peak of the emission spectrum is between 485 and 500 nm. The luminous intensity at 100°C remains at room temperature intensity of 90 to 95%, and the quantum efficiency is greater than 80%.

Benefits of technology

It realizes efficient luminescence of cyan nitrogen oxide fluorescent materials under purple light excitation, solves the problem of cyan cavity in white LED spectrum, improves the color rendering index, and is suitable for high display LED applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117586772B_ABST
    Figure CN117586772B_ABST
Patent Text Reader

Abstract

A cyan nitrogen oxide fluorescent material that can be excited by purple light and a preparation method thereof, wherein the chemical composition of the fluorescent material is: Ba 2‑ x Eu x Y4SiO7N2, where 0.05≤x≤0.2. The crystal structure of the matrix of this material belongs to the tetragonal system, with the space group of P4; 2+ As an activator, under the excitation of purple light, the luminous intensity of the cyan nitrogen oxide fluorescent material at 100°C is 0.90 to 0.95 times that at 25°C, the main peak of the emission spectrum is between 485 and 500nm, and the quantum efficiency is greater than 80%, so that the fluorescent material can be applied to white light LED devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of fluorescent materials, and in particular to a cyan nitrogen oxide fluorescent material that can be excited by purple light and a preparation method thereof. Background Art

[0002] Visible light is a type of electromagnetic spectrum visible to humans, and its wavelength range generally includes 380 to 780nm. In order to conveniently describe visible light of different wavelengths, people use colors to distinguish visible light. It is generally believed that: purple corresponds to 380 to 440nm; blue, 440 to 485nm; cyan, 485 to 500nm; green, 500 to 565nm; yellow, 565 to 570nm; orange, 590 to 620nm; red, 620 to 780nm. Sunlight can radiate a large amount of visible light. During the day and outdoors, humans can use the sun to gain vision, but indoors and at night, artificial visible light sources are needed.

[0003] At present, the commonly used visible light source is an electric light source, especially an LED white light source. Common white light LED implementation methods are to use blue light LED to excite yellow fluorescent materials (to obtain white light with a color temperature of ~6500K and a color rendering index of ~70), blue light LED to excite yellow + red fluorescent materials (to obtain white light with a color temperature of 3000K and a color rendering index of ~80), and blue light LED to excite green + red fluorescent materials (to obtain white light with a color temperature of ~4000K and a color rendering index of ~90). It is extremely difficult to obtain a higher color rendering index with the above scheme. This is because in the above scheme, the obtained spectral shape is quite different from the spectrum of sunlight, and the greater the difference in the spectrum, the lower the color rendering index. In comparison, the spectrum of conventional LED devices is mainly lacking in the cyan band, that is, there is a "trough" (corresponding to cyan) between the blue light and yellow light or / and green light emitted by the blue light chip. Compared with the solar spectrum, the continuity of the spectrum is poor, resulting in a low color rendering index. That is, patent document 1 (Chen Lei, Fermi, Chen Jie, He Liangrui, Tian Yunfei, Liu Yanfang, Zhang Qiang, A LED light source and lamp with a partial spectrum structure of sunlight visible light, CN107565006B) believes that: the current LED lighting source lacks a relatively large spectral component of 490nm cyan light. For this reason, patent document 2 (Li Li, Zhao Fuxing, Guan Xiaosheng, Zhang Lin, A long-life high-color white light LED light source, CN111403576B) discloses a method for obtaining a high (>90) color rendering index light source, which is characterized by using blue LED excitation + cyan + green or yellow + red fluorescent materials, which can replace the white LED light source composed of blue LED chips and yellow fluorescent powder, and meet the professional lighting fields such as photographic lighting and color detection that have high requirements for color reproduction. Furthermore, patent document 3 (Tang Wei, Liu Guoxu, Fu Xiquan, Shen Chongyu, A method for realizing white light LED with adjustable color temperature, adjustable color rendering index and adjustable brightness, CN109671836A) discloses a light source that can obtain a higher (>95) color rendering index, which is characterized by using purple LED excitation + blue + cyan + green + yellow + red fluorescent materials, mixing the different colors of light in the combination to produce full-spectrum white light, and obtaining an LED device with a spectrum close to that of sunlight (visible light).

[0004] It can be seen that cyan fluorescent materials are essential components for high color rendering white light LED lighting, and fluorescent materials that can be excited by purple light and emit cyan light are more meaningful for packaging high color rendering LEDs (purple LED excitation + blue + cyan + green + yellow + red fluorescent materials). For this reason, cyan fluorescent materials have been widely studied. For example, patent document 4 (Liang Hongbin, Liu Chunmeng, A cyan luminescent material and its preparation method, CN102899039A) discloses a cyan fluorescent material with a chemical formula of (4-x)SrO·4SiO 2 ·4SrCl 2xEuO cyan luminescent material, in which Eu 2+ is the activating ion; x is the molar amount of Eu replacing Sr, and the value range is: 0.01≤x≤0.50. Although the color coordinates of the emission spectrum of this material are in the cyan region, its corresponding excitation spectrum is vacuum ultraviolet light (147nm, 172nm) and low-voltage cathode rays (3kV, 25μA·cm -2 ), not purple light; at the same time, its chemical formula contains Cl, which is easily soluble in water and not resistant to moisture. The existing white light LED packaging form will inevitably be in a certain humidity environment, so it is difficult to apply this material to high-display LEDs. Similarly, patent document 5 (Jiao Huan, Lin Jizhou, Shi He, Bai Congrui, Han Xing, Wei Hengwei, Wang Xiaoming, Xu Ling, A broadband cyan light emitting CsCdCl 3 :xSb 3+ Single crystal and preparation method thereof, CN112266784B) discloses a broadband cyan emission ACdCl 3 :xSb 3+ Single crystal, where A represents Cs or Rb; 0.005≤x≤0.015. Under light excitation in the wavelength range of 250-380nm, the emission wavelength of the sample is in the range of 400-650nm, which belongs to broadband emission. Similarly, although the material can produce cyan light emission, the material contains Cs and Cl, which are easily soluble in water and not moisture-resistant. The existing white light LED packaging form will inevitably be in an environment with a certain humidity, so it is difficult to apply the material to high-display LEDs.

[0005] Based on the water resistance of the above materials, further, patent document 6 (Cheng Nanpu, Liu Yuqing, Tang Luomeng, Lin Yanjun, A cyan luminescent material, its preparation method and application, CN113563875B) discloses a cyan luminescent material with a chemical formula of Zn 4(1-x) O(BO 2 ) 6 :xPr 3+ A cyan luminescent material, wherein 0<x≤15%. The material has a sodalite cage structure and is chemically stable. Although the material can generate cyan light emission, the main peak of the emission spectrum of the material is located at 385nm, and the excitation spectrum is ultraviolet light, not violet light, so it is difficult to apply it to high-display LEDs. Similarly, non-patent document 1 (Fen Xiao, Rongxi Yi, Huiling Yuan, Guanjian Zang, Chengning Xie, Color tunable emission and energy transfer of Ce 3+ / Dy 3+ codoped Ba3 La 2 (BO 3 ) 4 phosphor for UV white LEDs, Spectrochimica Acta Part A: Molecular and Biomolecular Spectroscopy, 2018, 202: 352-358) also reported a chemical formula of Ba 3 La 2 (BO 3 ) 4 :Ce 3+ , under 350nm excitation, it can produce cyan light with a main peak of 458nm emission spectrum. Similarly, although the material can produce cyan light emission, the main peak of the emission spectrum of the material is at 350nm, and the excitation spectrum is ultraviolet light, not purple light, so it is difficult to apply it to high-display LEDs.

[0006] To this end, further, patent document 7 (Yin Yixuan, Li Xing, A cyan fluorescent material and its preparation method, CN106928259B) discloses a chemical formula of [K 2 Cd 2 Cl 2 L 2 (H 2 O) 5 ] n A cyan fluorescent material. The cyan fluorescent material is a 5-nitroorotic acid cadmium complex, where L is 5-nitroorotic acid with two protons H removed. Under the excitation of 400nm purple light, the material can produce a wide spectrum emission peak of cyan light, with the maximum emission peak located at 472nm. Although the material can emit cyan light and the excitation spectrum is also purple light, the material is a compound containing structural water, and the structure is unstable. It is easy to be dehydrated by heat and lose its luminescence performance. When the LED is working, it will generate a high temperature of ~100°C, so there are certain difficulties in applying the material to high-display LEDs.

[0007] Non-patent document 2 (Chen Hui, Li Haili, Zhang Na, Zhang Ruoyu, Research Progress of Silicon-based Nitrogen Oxide Phosphors for White Light LEDs, Functional Materials, 2017, 48(10):10042-10045) believes that nitrogen (oxygen) compound fluorescent materials have been widely studied and paid attention to in the application of white light LEDs due to their significant thermal stability, chemical stability, wide luminescence spectrum coverage and structural diversity. Therefore, high-performance cyan fluorescent materials can be found in nitrogen (oxygen) compounds. Taking nitrides as an example, non-patent document 3 (Chunpei Yan, Zhanning Liu, Weidong Zhuang, Ronghui Liu, Xianran Xing, Yuanhong Liu, Guantong Chen, Yanfeng Li, Xiaole Ma, YScSi 4 N 6 C:Ce 3+ —A BroadCyan-Emitting Phosphor To Weaken the Cyan Cavity in Full-Spectrum WhiteLight-Emitting Diodes, Inorganic Chemistry, 2017, 56(18):11087-11095) reported a Ce 3+ Doped YScSi 4 N 6 C nitride cyan fluorescent material. When excited in the 280-425nm band (including the violet range), this material can produce broadband cyan light emission with a peak wavelength of 469nm. 3+ Doped YScSi 4 N 6 C nitride cyan fluorescent material, green fluorescent material and red fluorescent material are packaged into white light LED, with a color rendering index of up to 94.7 and a color temperature of 4159K. Obviously, the cyan fluorescent material can effectively compensate for the cyan cavity in the LED spectrum and has potential application prospects in the field of full-spectrum lighting. However, it should be pointed out that the raw materials for synthesizing this fluorescent material include YH 3 , LaH 3 ScH 3 All raw material mixing operations need to be carried out in a glove box filled with purified nitrogen (H 2 O<1ppm and O 2 <100ppm), the synthesis temperature is as high as 1900℃; and the thermal quenching characteristics of the fluorescent material are general, the luminescence intensity of the optimal concentration sample at 100℃ is only ~50% of that at room temperature, while the common Y 3 Al5 O 12 :Ce yellow fluorescent material, the luminous intensity at 100°C is >95% of that at room temperature. Therefore, it is difficult to apply the cyan fluorescent material reported in Non-Patent Document 3 to high-display LEDs.

[0008] Non-patent document 4 (Hui-Li Li, Rong-Jun Xie, Guo-Hong Zhou, Naoto Hirosaki, Zhuo Sun, A Cyan-Emitting Basic 7 N 10 :Eu 2+ Phosphor Prepared by Gas Reduction and Nitridation for UV-Pumping White LEDs, Journal of The Electrochemical Society, 2010, 157(7): J251) reported a Eu 2+ Doped BaSi 7 N 10 Nitride cyan fluorescent material. Similarly, patent document 8 (Li Huili, Sun Zhuo, Zhang Zhejuan, Zhang Mingchang, Multi-component oxynitride-based or nitride-based phosphor and preparation method thereof, CN101629077A) discloses a multi-component oxynitride-based or nitride-based fluorescent material, whose luminescent wavelength covers the entire visible light region from blue light to red light: when the chemical composition is a general formula A: (MI 1-qx / p Re x ) y Si 12-(m+n) Al m+n O n N 16-n When the α-SiAlON:Re system is represented, the MI is one or two elements selected from Li, K, Mg, Ca, Sr, Y, La, Yb, and Lu; when the general formula B is: (MII 1-qx / 2 Re x ) 2 Si 5 N 8 When expressed as, the MII is one or two elements selected from Ca, Sr, and Ba; when represented by the general formula C: (MII 1-qx / 2 Re x )Si 7 N 10 When expressed as, MII is one or two elements among Ca, Sr, and Ba. The material corresponding to the general formula C is Eu 2+ Doped BaSi 7 N 10Nitride cyan fluorescent material. The main peak of its emission spectrum is located at 482-500nm. However, it should be pointed out that the main peak of the excitation spectrum of this fluorescent material is located at 300nm, not purple light. Therefore, it is difficult to apply the cyan fluorescent material reported in non-patent document 4 to high-display LEDs.

[0009] Non-Patent Literature 5 (Weibin Zhang, Yongwang Li, ShanShan Ye, Jiangcong Zhou, DewuWu, Chen Shi, Mengting Chen, Jianyan Ding, Quansheng Wu, Full-visible-spectrum lighting realized by a novel 2+ -doped nitride-based cyan-emitting phosphor, Dalton Transactions, 2021, 50:10446-10454) reported a Eu 2+ Doped Ca 2 BN 2 Cl nitride cyan fluorescent material. The main peak of the excitation spectrum of this material is at 350nm, which is near ultraviolet light, and the main peak of the emission spectrum is at 502nm, and the half-height width of the emission spectrum is 121nm. However, it should be pointed out that the main peak of the excitation spectrum of this fluorescent material is at 300nm, not violet light. Combining near-ultraviolet light chips with blue fluorescent materials, Ce 3+ Doped YScSi 4 N 6 C nitride cyan fluorescent material, green fluorescent material and red fluorescent material are packaged into a white light LED with a color rendering index of up to 92.4 and a color temperature of 3820K. In contrast, a white light LED is packaged with a near-ultraviolet chip combined with blue fluorescent material, green fluorescent material and red fluorescent material, with a color rendering index of 86.8 and a color temperature of 3695K. Obviously, the cyan fluorescent material can effectively compensate for the cyan cavity in the LED spectrum and has potential application prospects in the field of full-spectrum lighting. However, it should be pointed out that Eu 2+ Doped Ca 2 BN 2 The Cl nitride cyan fluorescent material contains Cl, and the material easily absorbs water and has an unstable structure. Therefore, it is difficult to apply the cyan fluorescent material reported in non-patent document 5 to high-display LEDs.

[0010] Patent document 9 (Wang Yuhua, Seto Xiaojun, Zhou Yuhan, A luminescent material and its preparation method and application, CN116716105A) discloses a luminescent material with a chemical formula of La 1-x Si 9Al 19 N 32 :xEu 2+ Cyan fluorescent material, wherein 0<x≤1. The luminescent material has a multilayer crystal structure, wherein La atoms are located in the M-La-M layer (M is Si / Al). 2+ Fully replace La 3+ , the luminous intensity increases abnormally. 2+ The optimal emission peak is red-shifted from 455 to 482 nm due to the doping, and the emission is transferred from blue light to cyan light. When combined with the near-ultraviolet LED chip, it can make up for the cyan cavity in the white light LED, and can produce white light with higher color rendering index and external quantum efficiency. However, it should be pointed out that the raw materials for synthesizing the fluorescent material include LaN, which is extremely unstable in chemical properties and expensive. The synthesis requires a nitrogen pressure of 0.5 to 0.7 MPa and a temperature of up to 1700 to 1800 ° C. Obviously, it is difficult to manufacture the material disclosed in patent document 9.

[0011] Taking nitrogen oxides as an example, non-patent literature 6 (Li Liyu, Shi Qiufeng, Guo Haijie, Cui Cai'e, Huang Ping, Wang Lei, Eu 2+ Doped MgY 2 Al 3 Si 2 O 11 Preparation and Luminescence Properties of Cyan Phosphors, Journal of Inorganic Chemistry, 2023, 39(1):63-70) reported a Eu 2+ Doped MgY 2 Al 3 Si 2 O 11 N cyan fluorescent material. When excited by 365nm ultraviolet light, the fluorescent material exhibits asymmetric broadband emission in the cyan region with a peak at 490nm, which can effectively provide cyan components for white light emitting diodes excited by ultraviolet chips. However, it should be pointed out that the main peak of the excitation spectrum of this fluorescent material is located at ~325nm, not violet light; the luminescence intensity of the optimal concentration sample at 100℃ is only ~65% of that at room temperature, while the common Y 3 Al 5 O 12 :Ce yellow fluorescent material, the luminous intensity at 100°C is >95% of that at room temperature. Therefore, it is difficult to apply the cyan fluorescent material reported in Non-Patent Document 6 to high-display LEDs.

[0012] Patent document 10 (Ge Wanyin, Lu Chenhui, Xu Meimei, Zhang Panfeng, Zhang Wei, a β-sialon (Si 5 AlON 7 ) cyan luminescent phosphor and its synthesis method and application, CN113583664A) discloses a Eu2+ Doped β-sialon (Si 5 AlON 7 ) Cyan luminescent fluorescent material. When excited by 365nm ultraviolet light, the emission spectrum of this material is mainly concentrated at 550nm (green light), and a blue light emission appears at 450nm. That is, this material is a visually cyan luminescent material, and the emission of green light + blue light produces a cyan effect. Since the main peak of the excitation spectrum of this fluorescent material is at 365nm (near ultraviolet), it is not purple light. Therefore, it is difficult to apply the cyan fluorescent material reported in Patent Document 9 to high-display LEDs.

[0013] Patent document 11 (Liu Quanlin, Dou Chao, Song Zhen, A violet light excited aluminum oxynitride blue cyan phosphor and its preparation and application, CN115305084A) discloses a violet light excited aluminum oxynitride blue cyan phosphor with a chemical formula of Ba 1-x Eu x Al 11 O 17.5-(3y+z) / 2 N y F z Aluminum oxide nitrogen compound blue-cyan fluorescent material, wherein 0.01≤x≤0.20; 0.4<y≤5.0; 0≤z≤2.0. Under the excitation of violet light, the main peak of the emission spectrum of the blue-cyan phosphor is in the range of 460-480nm. As y increases, its excitation band can be broadened to 440nm, which can match well with the 380-420nm violet light chip. However, it should be pointed out that the synthesis temperature of this material is relatively high, at 1500-1700℃. In addition, the component contains F, and fluoride is easily soluble in water. Therefore, it is difficult to manufacture the material corresponding to patent document 11, and it is also difficult to apply it to high-display LEDs.

[0014] In fact, the cyan fluorescent material widely used in the market is patent document 12 (Zhou Zhixian, Fan Xiaoming, lamp, CN212644312U), which discloses: a chemical formula of BaSi 2 N 2 O 2 :Eu 2+ For example, patent document 13 (You Hongpeng, Song Yanhua, Hong Guangyan, A field emission phosphor and its preparation method, CN101717638A) discloses a phosphor with the chemical formula: 1-x Si 2 O 2 N 2:xEu nitride oxide fluorescent material, wherein 0<x≤0.2; A is at least one of Ba and Sr, and Ba and Sr are in any molar ratio. The material is sintered at 1200°C for 2 hours in a reducing atmosphere or nitrogen, and then sintered at 1500-1550°C for 2-6 hours in a reducing atmosphere or nitrogen. Under violet light excitation, its emission spectrum is adjustable between 490 and 532nm. Patent document 14 (Zhang Liangliang, He Shuai, Zhang Jiahua, Zhang Xia, Hao Zhendong, Pan Guohui, Wu Huajun, Fluorescence enhanced silicon-based nitride oxide cyan phosphor and preparation method thereof, WO2019061004A1) discloses an enhanced silicon-based nitride oxide BaSi 2 O 2 N 2 :Eu 2+ The method of measuring the luminous intensity of cyan fluorescent material, whose chemical formula is (Ba l-x-y-z-m M x R y A z )O·0.5SiO 2 0.5Si 3 N 4 :mEu 2+ , 0.01≤m≤0.05, 0≤x≤0.2, 0.005≤y≤0.2, 0.5≤y / z≤1, 0<x+y+z<0.5, R is at least one of La, Y, Tb, Dy, Ho, Er, Tm, Yb, Lu, Bi, Pr, Mn; M is at least one of Ca, Sr, Mg; A is at least one of K, Na, Li. The fluorescent material has high luminous intensity, and the excitation peak is stable at 490-500nm under (purple) blue light excitation. However, it should be pointed out that, as shown in non-patent document 7 (Volker Bachmann, Cees Ronda, Oliver Oeckler, Wolfgang Schnick, Andries Meijerink, Color Point Tuning for (Sr, Ca, Ba) Si 2 O 2 N 2 :Eu 2+ for White Light LEDs, Chemistry of Materials, 2009, 21(2):316-325), Non-Patent Literature 8 (Shuai He, Liangliang Zhang, Xueqing Liu, Dashuai Sun, Hao Wu, Huajun Wu, Guohui Pan, Zhendong Hao, Jiahua Zhang, Luminescent enhancement of cyanBaSi 2 O2 N 2 :Eu 2+ phosphor by addition of Ho 3+ , Journal of Materials Science:Materials in Electronics, 2022, 33:14972-14978) and non-patent literature 9 (Lei Chen, Zhuming Cheng, Guifang Zheng, Gang Yao, Liangrui He, Lei Wang, Jianzhe Liu, Haiwu Zheng, Shizhong Wei, Haiyong Ni, A third route to synthesis of green phosphorSrSi 2 O 2 N 2 :Eu 2+ from SrO, Journal of Luminescence, 2021, 230:117729) pointed out that the cyan fluorescent material BaSi 2 O 2 N 2 :Eu 2+ There are many problems at present, such as the thermal quenching characteristics of the material are generally poor, its luminous intensity at 100°C is 85% of that at room temperature, and the common Y 3 Al 5 O 12 : Ce yellow fluorescent material, the luminous intensity at 100℃ is >95% of that at room temperature; the quantum efficiency is low, only ~80%, while the common Y 3 Al 5 O 12 : The quantum efficiency of Ce yellow fluorescent material is >95%; the stability is poor and it is easily oxidized, such as non-patent document 10 (Yujie Zhao, Xiao Wang, Quan-an Li, Xinyu Zhang, Ye Li, Rong-Jun Xie, J. Ruud van Ommen, HT Tintzen, Enhancing thermal degradation stability of BaSi 2 O 2 N 2 :Eu 2+ for white light-emitting diodes byultra-thin Al 2 O 3According to a report by the Institute of Materials Science and Engineering (IMS), after ~300 h of use (450 nm blue LED package), the luminous intensity of the material dropped to ~25% of the initial value, even with the use of Al 2 O 3 After encapsulation to avoid oxidation, the luminous intensity still dropped to 75% of the initial value after ~300h of use (450nm blue LED package).

[0015] In short, there is still a lack of cyan fluorescent materials with excellent performance under violet light excitation (the main peak of the emission spectrum is between 485 and 500 nm; the luminous intensity at 100°C is 0.90 to 0.95 times that at 25°C; the quantum efficiency is greater than 80%). 2-x Eu x Y 4 SiO 7 N 2 (0.05≤x≤0.2, the crystal structure of the corresponding matrix belongs to the tetragonal system, and the space group is P4) The cyan luminescence property under violet light excitation is disclosed for the first time in the present invention. Summary of the invention

[0016] To this end, the first object of the present invention is to provide a cyan oxynitride fluorescent material that can be excited by violet light. 2+ It is an activator. Under the excitation of violet light, the main peak of the emission spectrum is located between 485 and 500 nm. The luminous intensity at 100°C is 0.90 to 0.95 times that at 25°C, and the quantum efficiency is greater than 80%. The crystal structure of the corresponding matrix of the cyan nitrogen oxide fluorescent material that can be excited by violet light belongs to the tetragonal system, and the space group is P4.

[0017] To achieve the above object, the present invention adopts the following technical solution:

[0018] A cyan nitrogen oxide fluorescent material that can be excited by purple light, the chemical formula of the material is:

[0019] Ba 2-x Eu x Y 4 SiO 7 N 2

[0020] Among them, 0.05≤x≤0.2.

[0021] Preferably, the x may be 0.1.

[0022] The second object of the present invention is to provide a method for preparing a cyan oxynitride fluorescent material that can be excited by violet light. The preparation method comprises the following steps: mixing a Ba precursor, a Eu precursor, a Y precursor and a Si precursor, and performing a high-temperature solid-phase reaction in an ammonia atmosphere to obtain a cyan oxynitride fluorescent material that can be excited by violet light.

[0023] Preferably, in this step, the molar ratio of Ba, Eu, Y and Si in the Ba precursor, Eu precursor, Y precursor and Si precursor is (2-x):x:4:1, wherein 0.05≤x≤0.2.

[0024] Preferably, in this step, the Ba precursor is selected from one or more of Ba carbonate, Ba oxide, Ba oxalate and Ba nitrate; the Eu precursor is selected from one or more of Eu carbonate, Eu oxide, Eu oxalate and Eu nitrate; the Y precursor is selected from one or more of Y carbonate, Y oxide, Y oxalate and Y nitrate; the Si precursor is selected from one or more of Si 3 N 4 .

[0025] Preferably, the purity of the Ba precursor, Eu precursor, Y precursor and Si precursor is not less than 99.5%.

[0026] Preferably, in the above steps, the temperature of the high temperature solid phase reaction is between 1350°C and 1450°C, the atmosphere is ammonia, and the time of the high temperature solid phase reaction is between 4 and 10 hours.

[0027] Another object of the present invention is to provide a white light LED light source. The white light LED light source comprises at least a chemical formula of Ba 2-x Eu x Y 4 SiO 7 N 2 (wherein 0.05≤x≤0.2) and an LED chip capable of emitting light between 380 and 420 nm.

[0028] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0029] Compared with the prior art, the method implemented in the present invention prepares a cyan nitrogen oxide fluorescent material that can be excited by purple light. The chemical composition of the fluorescent material is: Ba 2-x Eu x Y 4 SiO 7 N 2 , where 0.05≤x≤0.2. The crystal structure of the matrix of this material belongs to the tetragonal system, with the space group being P4;2+ As an activator, under the excitation of purple light, the luminous intensity of the cyan nitrogen oxide fluorescent material at 100°C is 0.90 to 0.95 times that at 25°C, the main peak of the emission spectrum is between 485 and 500nm, and the quantum efficiency is greater than 80%, so that the fluorescent material can be applied to white light LED devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is the emission spectrum of the material obtained in Comparative Example 1 under 400nm excitation.

[0031] Figure 2 This is the X-ray diffraction pattern of the material obtained in Comparative Example 1.

[0032] Figure 3 This is the emission spectrum of the material obtained in Comparative Example 2 under 400nm excitation.

[0033] Figure 4 This is the emission spectrum of the material obtained in Comparative Example 3 under 400nm excitation.

[0034] Figure 5 This is the emission spectrum of the material obtained in Comparative Example 4 under 400nm excitation.

[0035] Figure 6 This is the emission spectrum of the material obtained in Comparative Example 5 under 400nm excitation.

[0036] Figure 7 This is the emission spectrum of the material obtained in Comparative Example 6 under 400nm excitation.

[0037] Figure 8 This is the emission spectrum of the material obtained in Comparative Example 7 under 400nm excitation.

[0038] Fig. 9 This is the emission spectrum of the material obtained in Comparative Example 8 under 400nm excitation.

[0039] Fig.10 This is the emission spectrum of the material obtained in Comparative Example 9 under 400nm excitation.

[0040] Fig.11 This is the emission spectrum of the luminescent material obtained in Example 1 under 400nm excitation.

[0041] Fig.12 The emission spectrum of the luminescent material obtained in Example 6 under 400nm excitation and the corresponding excitation spectrum.

[0042] Fig.13 This is a comparison chart of the luminescent intensity of the luminescent material obtained in Example 6 at different temperatures.

[0043] Fig.14 This is the spectrum diagram of the white light LED device obtained in Example 11. DETAILED DESCRIPTION

[0044] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.

[0045] The present invention provides a cyan nitrogen oxide fluorescent material that can be excited by purple light, and its chemical formula is as follows:

[0046] Ba 2-x Eu x Y 4 SiO 7 N 2

[0047] Among them, 0.05≤x≤0.2.

[0048] In one embodiment of the present invention, the x is preferably 0.05; in one embodiment of the present application, the x is preferably 0.06; in one embodiment of the present invention, the x is preferably 0.07; in one embodiment of the present invention, the x is preferably 0.08; in one embodiment of the present invention, the x is preferably 0.09; in one embodiment of the present invention, the x is preferably 0.1; in one embodiment of the present invention, the x is preferably 0.12; in one embodiment of the present invention, the x is preferably 0.15; in one embodiment of the present invention, the x is preferably 0.18; in another embodiment of the present invention, the x is preferably 0.2.

[0049] The present invention also provides a method for preparing a cyan nitride fluorescent material that can be excited by violet light, the steps of which are as follows: mixing a Ba precursor, a Eu precursor, a Y precursor and a Si precursor, and performing a high-temperature solid-phase reaction in an ammonia atmosphere to obtain a cyan nitride fluorescent material that can be excited by violet light.

[0050] In the above steps, the molar ratio of Ba, Eu, Y and Si in the Ba precursor, Eu precursor, Y precursor and Si precursor is (2-x):x:4:1, wherein 0.05≤x≤0.2.

[0051] In the above steps, the Ba precursor can be a compound containing Ba known in the art without any special limitation. In the present invention, it is preferably one or more of Ba carbonate, Ba oxide, Ba oxalate and Ba nitrate, and more preferably Ba carbonate, i.e., BaCO 3 The Eu precursor may be selected from one or more of Eu carbonate, Eu oxide, Eu oxalate and Eu nitrate, more preferably Eu oxide, i.e. Eu 2 O 3The Y precursor can be selected from one or more of a carbonate of Y, an oxide of Y, an oxalate of Y and a nitrate of Y, more preferably an oxide of Y, i.e., Y 2 O 3 ; The Si precursor is selected from Si 3 N 4 .

[0052] The purity of the above-mentioned Ba precursor, Eu precursor, Y precursor and Si precursor is not less than 99.5%. The higher the purity, the less impurities in the obtained fluorescent material.

[0053] In the above steps, the temperature of the high-temperature solid phase is preferably 1350-1450°C, and the atmosphere is an ammonia atmosphere; in some embodiments provided by the present invention, the temperature of the high-temperature solid phase is preferably 1400°C.

[0054] The high temperature solid phase time in the above steps is preferably 4 to 10 hours, more preferably 5 to 8 hours; in some embodiments provided by the present invention, the high temperature solid phase time is preferably 6 hours.

[0055] The high temperature solid phase reaction is preferably carried out in a high temperature furnace. After the reaction is carried out, the furnace is cooled to room temperature to obtain a cyan nitrogen oxide fluorescent material that can be excited by purple light.

[0056] The embodiment of the present invention adopts a high temperature solid phase reaction to successfully prepare a cyan nitrogen oxide fluorescent material that can be excited by purple light.

[0057] The present invention also provides a white light LED light source. The white light LED light source comprises at least one cyan nitrogen oxide fluorescent material (corresponding to the chemical formula of Ba 2-x Eu x Y 4 SiO 7 N 2 , wherein 0.05≤x≤0.2) and an LED chip that can generate light between 380 and 420 nm. The specific production steps include: mixing a blue fluorescent material that can be excited by purple light, a cyan nitrogen oxide fluorescent material (the present invention), a green fluorescent material, a yellow fluorescent material, and a red fluorescent material with an epoxy resin, applying the mixture to the surface of an LED chip that can generate light between 380 and 420 nm, and then curing the mixture at 150°C for 2 hours to obtain a white light LED light source.

[0058] In order to further illustrate the present invention, a cyan nitrogen oxide fluorescent material that can be excited by purple light and a preparation method thereof provided by the present invention are described in detail below in conjunction with embodiments.

[0059] The reagents used in the following comparative examples and embodiments are all commercially available.

[0060] Comparative Example 1

[0061] The raw material is BaCO 3 , Y 2 O 3 and Si 3 N 4 , BaCO 3 , Y 2 O 3 and Si 3 N 4 The molar ratio of Ba, Y and Si in the crucible is 2:4:1. After the above raw materials are ground and mixed, they are put into a crucible and sintered at 1400℃ for 6h in a high temperature furnace under an ammonia atmosphere. After cooling to room temperature, the theoretical chemical composition is Ba. 2 Y 4 SiO 7 N 2 materials.

[0062] The material obtained in Comparative Example 1 was analyzed using a fluorescence spectrometer. Since no luminescent center was doped, the material did not emit light under light excitation of different wavelengths. Figure 1 As shown (violet light 400nm excitation). See Table 1 for details. The material obtained in Comparative Example 1 was subjected to X-ray diffraction analysis using an X-ray diffractometer, and its X-ray diffraction spectrum is as follows Figure 2 The results of structural refinement show that the crystal structure of the nitride oxide material (matrix) belongs to the tetragonal system and the space group is P4.

[0063] Comparative Example 2

[0064] The raw material is BaCO 3 、Eu 2 O 3 , Y 2 O 3 and Si 3 N 4 , BaCO 3 、Eu 2 O 3 , Y 2 O 3 and Si 3 N 4 The molar ratio of Ba, Eu, Y and Si in the sample is 1.98:0.02:4:1. The raw materials are ground and mixed, then put into a crucible and sintered at 1400℃ for 6h in a high temperature furnace under an ammonia atmosphere. The theoretical chemical composition is Ba 1.98 Eu 0.02 Y 4 SiO 7 N 2 materials.

[0065] The fluorescent material obtained in Comparative Example 2 was analyzed using a fluorescence spectrometer to obtain its emission spectrum. Figure 3 As shown. Due to the low concentration of Eu doping in this material, under the excitation of 400nm purple light, the main peak of the emission spectrum of this material is located at 468nm, which is blue light emission; the quantum efficiency tester is used to test the quantum efficiency of the material corresponding to comparative example 2, and the quantum efficiency is 66.5%, which is a low value; the luminescence intensity of the material at different temperatures is measured using a luminescent material thermal quenching performance tester, and it is found that the luminescence intensity of this material at 100℃ under the excitation of 400nm purple light is 0.91 times that at 25℃, as shown in Table 1. It can be seen that comparative example 2 is not a cyan nitrogen oxide fluorescent material that can be excited by purple light, but a fluorescent material that emits blue light.

[0066] Comparative Example 3

[0067] The raw material is BaCO 3 、Eu 2 O 3 , Y 2 O 3 and Si 3 N 4 , BaCO 3 、Eu 2 O 3 , Y 2 O 3 and Si 3 N 4 The molar ratio of Ba, Eu, Y and Si in the sample is 1.75:0.25:4:1. The raw materials are ground and mixed, then put into a crucible and sintered at 1400℃ for 6h in a high temperature furnace under an ammonia atmosphere. The theoretical chemical composition is Ba 1.75 Eu 0.25 Y 4 SiO 7 N 2 materials.

[0068] The fluorescent material obtained in Comparative Example 3 was analyzed using a fluorescence spectrometer to obtain its emission spectrum. Figure 4As shown. Due to the high concentration of Eu doping in this material, under the excitation of 400nm purple light, the main peak of the emission spectrum of this material is located at 510nm, which is green light. The quantum efficiency tester is used to test the quantum efficiency of the material corresponding to Comparative Example 3, and the quantum efficiency is 70.3%, which is relatively low. The luminous intensity of the material at different temperatures is measured using a luminescent material thermal quenching performance tester. It is found that the luminous intensity of the material at 100℃ under the excitation of 400nm purple light is 0.88 times that at 25℃, as shown in Table 1. It can be seen that Comparative Example 3 is not a cyan nitrogen oxide fluorescent material that can be excited by purple light, but a green fluorescent material.

[0069] Comparative Example 4

[0070] The raw material is BaCO 3 、Eu 2 O 3 , Y 2 O 3 and SiO 2 , BaCO 3 、Eu 2 O 3 , Y 2 O 3 and SiO 2 The molar ratio of Ba, Eu, Y and Si in the sample is 1.9:0.1:4:1. The raw materials are ground and mixed, then put into a crucible and sintered at 1400℃ for 6h in a high temperature furnace under an ammonia atmosphere. The theoretical chemical composition is Ba 1.9 Eu 0.1 Y 4 SiO 7 N 2 materials.

[0071] The fluorescent material obtained in Comparative Example 4 was analyzed using a fluorescence spectrometer to obtain its emission spectrum. Figure 5 As shown. Since all the sources of Si are SiO 2 , instead of Si 3 N 4Therefore, under the excitation of 400nm purple light, the main peak of the emission spectrum of the material is located at 522nm, which is green light (obviously the source of Si will eventually affect the structure of the material and change the crystal field environment around Eu, resulting in changes in the luminescence properties of the material); the quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Comparative Example 4, and the quantum efficiency was 18.7%, which is a relatively low value; the luminescence intensity of the material at different temperatures was measured using a luminescent material thermal quenching performance tester, and it was found that the luminescence intensity of the material at 100°C under the excitation of 400nm purple light was 0.42 times that at 25°C, which indicates that the thermal quenching property of the material is poor, as shown in Table 1. It can be seen that Comparative Example 4 is not a cyan nitrogen oxide fluorescent material that can be excited by purple light, but a green fluorescent material.

[0072] Comparative Example 5

[0073] The raw material is BaCO 3 、Eu 2 O 3 , Y 2 O 3 , YN and SiO 2 , BaCO 3 、Eu 2 O 3 , Y 2 O 3 , YN and SiO 2 The molar ratio of Ba, Eu, Y and Si in the sample is 1.9:0.1:2:2:1. The raw materials are ground and mixed in a glove box, then put into a crucible and sintered at 1400°C for 6h in a high temperature furnace under an ammonia atmosphere. The theoretical chemical composition is Ba 1.9 Eu 0.1 Y 4 SiO 7 N 2 of fluorescent materials.

[0074] The fluorescent material obtained in Comparative Example 5 was analyzed using a fluorescence spectrometer to obtain its emission spectrum. Figure 6 As shown. Since the entire source of N is YN, not Si 3 N 4and ammonia atmosphere, so the main peak of the emission spectrum of the material under the excitation of violet light 400nm is located at 465nm, which is blue light luminescence (obviously the source of N will eventually affect the structure of the material and change the crystal field environment around Eu, resulting in changes in the luminescence properties of the material); the quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Comparative Example 5, and the quantum efficiency was 33.6%; the luminescence intensity of the material at different temperatures was measured using a luminescent material thermal quenching performance tester, and it was found that the luminescence intensity of the material at 100°C under the excitation of violet light 400nm was 0.57 times that at 25°C, which indicates that the thermal quenching property of the material is poor, as shown in Table 1. It can be seen that Comparative Example 5 is not a cyan nitrogen oxide fluorescent material that can be excited by violet light, but a fluorescent material that emits blue light.

[0075] Comparative Example 6

[0076] The raw material is BaCO 3 、SrCO 3 、Eu 2 O 3 , Y 2 O 3 and Si 3 N 4 , BaCO 3 、SrCO 3 、Eu 2 O 3 , Y 2 O 3 and Si 3 N 4 The molar ratio of Ba, Sr, Eu, Y and Si in the sample is 0.9:1:0.1:4:1. The raw materials are ground and mixed, then put into a crucible, sintered at 1400℃ for 6h in a high temperature furnace under an ammonia atmosphere, and cooled to room temperature to obtain a theoretical chemical composition of Ba. 0.9 S E 0.1 Y 4 SiO 7 N 2 of fluorescent materials.

[0077] The fluorescent material obtained in Comparative Example 6 was analyzed using a fluorescence spectrometer to obtain its emission spectrum. Figure 7As shown. Since part of Ba is replaced by Sr, the main peak of the emission spectrum of the material under the excitation of 400nm purple light is located at 535nm, which is green light (obviously replacing Ba with Sr will eventually affect the structure of the material and change the crystal field environment around Eu, resulting in changes in the luminescence properties of the material); the quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Comparative Example 6, and the quantum efficiency was 27.3%, which is low; the luminescence intensity of the material at different temperatures was measured using a luminescent material thermal quenching performance tester, and it was found that the luminescence intensity of the material at 100°C under the excitation of 400nm purple light was 0.36 times that at 25°C, which indicates that the thermal quenching property of the material is poor, as shown in Table 1. It can be seen that Comparative Example 6 is not a cyan nitrogen oxide fluorescent material that can be excited by purple light, but a green fluorescent material.

[0078] Comparative Example 7

[0079] The raw material is BaCO 3 、Eu 2 O 3 , Y 2 O 3 Sc 2 O 3 and Si 3 N 4 , BaCO 3 、Eu 2 O 3 , Y 2 O 3 Sc 2 O 3 and Si 3 N 4 The molar ratio of Ba, Eu, Y, Sc and Si in the sample is 1.9:0.1:2:2:1. The raw materials are ground and mixed, then put into a crucible, sintered at 1400℃ for 6h in a high temperature furnace under an ammonia atmosphere, and cooled to room temperature to obtain a theoretical chemical composition of Ba. 1.9 Eu 0.1 Y 2 Sc 2 SiO 7 N 2 of fluorescent materials.

[0080] The fluorescent material obtained in Comparative Example 7 was analyzed using a fluorescence spectrometer to obtain its emission spectrum. Figure 8As shown. Since Sc replaces part of Y, the main peak of the emission spectrum of the material under the excitation of 400nm purple light is located at 569nm, which is yellow light (obviously, the replacement of Y by Sc will eventually affect the structure of the material and the crystal field environment around Eu, resulting in changes in the luminescence properties of the material); the quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Comparative Example 7, and the quantum efficiency was 11.8%, which is low; the luminescence intensity of the material at different temperatures was measured using a luminescent material thermal quenching performance tester, and it was found that the luminescence intensity of the material at 100°C under the excitation of 400nm purple light was 0.18 times that at 25°C, which indicates that the thermal quenching property of the material is poor, as shown in Table 1. It can be seen that Comparative Example 7 is not a cyan nitrogen oxide fluorescent material that can be excited by purple light, but a yellow fluorescent material.

[0081] Comparative Example 8

[0082] The raw material is BaCO 3 、Eu 2 O 3 , Y 2 O 3 and Si 3 N 4 , BaCO 3 、Eu 2 O 3 , Y 2 O 3 and Si 3 N 4 The molar ratio of Ba, Eu, Y and Si in the sample is 1.9:0.1:4:1. The raw materials are ground and mixed, then put into a crucible and sintered at 1400℃ for 6h in a high temperature furnace under nitrogen atmosphere. The theoretical chemical composition is Ba 1.9 Eu 0.1 Y 4 SiO 7 N 2 of fluorescent materials.

[0083] The fluorescent material obtained in Comparative Example 8 was analyzed using a fluorescence spectrometer to obtain its emission spectrum. Fig. 9As shown. Under the excitation of 400nm purple light, the main peak of the emission spectrum of the material is located at 491nm; because the more reducing ammonia atmosphere was not used, the quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Comparative Example 8, and the quantum efficiency was only 15.9%; the luminescence intensity of the material at different temperatures was measured using a luminescent material thermal quenching performance tester, and it was found that the luminescence intensity of the material at 100°C under the excitation of 400nm purple light was 0.45 times that at 25°C, as shown in Table 1. It can be seen that although Comparative Example 8 is a cyan nitrogen oxide fluorescent material that can be excited by purple light, its quantum efficiency is low, and there are certain difficulties in applying it to white light LED devices.

[0084] Comparative Example 9

[0085] The raw material is BaCO 3 、Eu 2 O 3 , Y 2 O 3 and Si 3 N 4 , BaCO 3 、Eu 2 O 3 , Y 2 O 3 and Si 3 N 4 The molar ratio of Ba, Eu, Y and Si in the sample is 1.9:0.1:4:1. The raw materials are ground and mixed, then put into a crucible, and sintered at 1400°C for 6 hours in a high-temperature furnace under a nitrogen and hydrogen (volume ratio of 9:1) atmosphere. The sample is cooled to room temperature and the theoretical chemical composition is Ba. 1.9 Eu 0.1 Y 4 SiO 7 N 2 of fluorescent materials.

[0086] The fluorescent material obtained in Comparative Example 9 was analyzed using a fluorescence spectrometer to obtain its emission spectrum. Fig.10 As shown. Under the excitation of 400nm purple light, the main peak of the emission spectrum of the material is located at 490nm; because the more reducing ammonia atmosphere was not used, the quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Comparative Example 9, and the quantum efficiency was only 35.5%; the luminescent material thermal quenching performance tester was used to measure the luminous intensity of the material at different temperatures, and it was found that the luminous intensity of the material at 100℃ under the excitation of 400nm purple light was 0.37 times that at 25℃, as shown in Table 1. It can be seen that although Comparative Example 9 is a cyan nitrogen oxide fluorescent material that can be excited by purple light, its quantum efficiency is low, and there are certain difficulties in applying it to white light LED devices.

[0087] Example 1

[0088] The raw material is BaCO 3 、Eu 2 O 3 , Y 2 O 3 and Si 3 N 4 , BaCO 3 、Eu 2 O 3 , Y 2 O 3 and Si 3 N 4 The molar ratio of Ba, Eu, Y and Si in the sample is 1.95:0.05:4:1. The raw materials are ground and mixed, then put into a crucible and sintered at 1400℃ for 6h in a high temperature furnace under an ammonia atmosphere. The theoretical chemical composition is Ba 1.95 Eu 0.05 Y 4 SiO 7 N 2 of fluorescent materials.

[0089] The fluorescent material obtained in Example 1 was analyzed using a fluorescence spectrometer to obtain its emission spectrum. Fig.11 As shown. Under the excitation of 400nm purple light, the main peak of the emission spectrum of the material is located at 485nm; the quantum efficiency tester is used to test the quantum efficiency of the material corresponding to Example 1, and the quantum efficiency is 86.2%; the luminescence intensity of the material at different temperatures is measured using a luminescent material thermal quenching performance tester, and it is found that the luminescence intensity of the material at 100°C under the excitation of 400nm purple light is 0.93 times the luminescence intensity at 25°C, as shown in Table 1. It can be seen that Example 1 is a cyan nitrogen oxide fluorescent material that can be excited by purple light. Under the excitation of 400nm purple light, the main peak of the emission spectrum of the cyan nitrogen oxide fluorescent material is located between 485 and 500nm; the luminescence intensity of the cyan nitrogen oxide fluorescent material that can be excited by purple light at 100°C is 0.90 to 0.95 times the luminescence intensity at 25°C; the quantum efficiency of the cyan nitrogen oxide fluorescent material that can be excited by purple light under purple light excitation is greater than 80%, so that the fluorescent material is applied to white light LED devices.

[0090] Example 2

[0091] The raw material is BaCO 3 、Eu 2 O 3 , Y 2 O 3 and Si 3 N 4 , BaCO 3、Eu 2 O 3 , Y 2 O 3 and Si 3 N 4 The molar ratio of Ba, Eu, Y and Si in the sample is 1.94:0.06:4:1. The raw materials are ground and mixed, then put into a crucible and sintered at 1400℃ for 6h in a high temperature furnace under an ammonia atmosphere. The theoretical chemical composition is Ba 1.94 Eu 0.06 Y 4 SiO 7 N 2 of fluorescent materials.

[0092] The fluorescent material obtained in Example 2 was analyzed by using a fluorescence spectrometer, and it was found that the main peak of the emission spectrum of the material under the excitation of 400nm purple light was located at 485nm; the quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Example 2, and the quantum efficiency was 81.6%; the luminescence intensity of the material at different temperatures was measured by using a luminescent material thermal quenching performance tester, and it was found that the luminescence intensity of the material at 100°C under the excitation of 400nm purple light was 0.92 times the luminescence intensity at 25°C, as shown in Table 1. It can be seen that Example 2 is a cyan nitrogen oxide fluorescent material that can be excited by purple light. Under the excitation of 400nm purple light, the main peak of the emission spectrum of the cyan nitrogen oxide fluorescent material is located between 485 and 500nm; the luminescence intensity of the cyan nitrogen oxide fluorescent material that can be excited by purple light at 100°C is 0.90 to 0.95 times the luminescence intensity at 25°C; the quantum efficiency of the cyan nitrogen oxide fluorescent material that can be excited by purple light under purple light excitation is greater than 80%, so that the fluorescent material is applied to white light LED devices.

[0093] Example 3

[0094] The raw material is BaCO 3 、Eu 2 O 3 , Y 2 O 3 and Si 3 N 4 , BaCO 3 、Eu 2 O 3 , Y 2 O 3 and Si 3 N 4 The molar ratio of Ba, Eu, Y and Si in the sample is 1.93:0.07:4:1. The raw materials are ground and mixed, then put into a crucible and sintered at 1400℃ for 6h in a high temperature furnace under an ammonia atmosphere. The theoretical chemical composition is Ba1.93 Eu 0.07 Y 4 SiO 7 N 2 of fluorescent materials.

[0095] The fluorescent material obtained in Example 3 was analyzed by using a fluorescence spectrometer, and it was found that the main peak of the emission spectrum of the material under the excitation of 400nm purple light was located at 486nm; the quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Example 3, and the quantum efficiency was 82.9%; the luminescence intensity of the material at different temperatures was measured by using a luminescent material thermal quenching performance tester, and it was found that the luminescence intensity of the material at 100°C under the excitation of 400nm purple light was 0.94 times that at 25°C, as shown in Table 1. It can be seen that Example 3 is a cyan nitrogen oxide fluorescent material that can be excited by purple light. Under the excitation of 400nm purple light, the main peak of the emission spectrum of the cyan nitrogen oxide fluorescent material is located between 485 and 500nm; the luminescence intensity of the cyan nitrogen oxide fluorescent material that can be excited by purple light at 100°C is 0.90 to 0.95 times that at 25°C; the quantum efficiency of the cyan nitrogen oxide fluorescent material that can be excited by purple light under purple light excitation is greater than 80%, so that the fluorescent material is applied to white light LED devices.

[0096] Example 4

[0097] The raw material is BaCO 3 、Eu 2 O 3 , Y 2 O 3 and Si 3 N 4 , BaCO 3 、Eu 2 O 3 , Y 2 O 3 and Si 3 N 4 The molar ratio of Ba, Eu, Y and Si in the sample is 1.92:0.08:4:1. The raw materials are ground and mixed, then put into a crucible and sintered at 1400℃ for 6h in a high temperature furnace under an ammonia atmosphere. The theoretical chemical composition is Ba 1.92 Eu 0.08 Y 4 SiO 7 N 2 of fluorescent materials.

[0098] The fluorescent material obtained in Example 4 was analyzed by using a fluorescence spectrometer, and it was found that the main peak of the emission spectrum of the material under the excitation of 400nm purple light was located at 488nm; the quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Example 4, and the quantum efficiency was 89.2%; the luminescence intensity of the material at different temperatures was measured using a luminescent material thermal quenching performance tester, and it was found that the luminescence intensity of the material under the excitation of 400nm purple light at 100°C was 0.91 times the luminescence intensity at 25°C, as shown in Table 1. It can be seen that Example 4 is a cyan nitrogen oxide fluorescent material that can be excited by purple light. Under the excitation of 400nm purple light, the main peak of the emission spectrum of the cyan nitrogen oxide fluorescent material is located between 485 and 500nm; the luminescence intensity of the cyan nitrogen oxide fluorescent material that can be excited by purple light at 100°C is 0.90 to 0.95 times the luminescence intensity at 25°C; the quantum efficiency of the cyan nitrogen oxide fluorescent material that can be excited by purple light under purple light excitation is greater than 80%, so that the fluorescent material is applied to white light LED devices.

[0099] Example 5

[0100] The raw material is BaCO 3 、Eu 2 O 3 , Y 2 O 3 and Si 3 N 4 , BaCO 3 、Eu 2 O 3 , Y 2 O 3 and Si 3 N 4 The molar ratio of Ba, Eu, Y and Si in the sample is 1.91:0.09:4:1. The raw materials are ground and mixed, then put into a crucible and sintered at 1400℃ for 6h in a high temperature furnace under an ammonia atmosphere. The theoretical chemical composition is Ba 1.91 Eu 0.09 Y 4 SiO 7 N 2 of fluorescent materials.

[0101] The fluorescent material obtained in Example 5 was analyzed by using a fluorescence spectrometer, and it was found that the main peak of the emission spectrum of the material under the excitation of 400nm purple light was located at 489nm; the quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Example 5, and the quantum efficiency was 89.5%, as shown in Table 1; the luminescence intensity of the material at different temperatures was measured by using a luminescent material thermal quenching performance tester, and it was found that the luminescence intensity of the material at 100°C under the excitation of 400nm purple light was 0.93 times the luminescence intensity at 25°C. It can be seen that Example 5 is a cyan nitrogen oxide fluorescent material that can be excited by purple light. Under the excitation of 400nm purple light, the main peak of the emission spectrum of the cyan nitrogen oxide fluorescent material is located between 485 and 500nm; the luminescence intensity of the cyan nitrogen oxide fluorescent material that can be excited by purple light at 100°C is 0.90 to 0.95 times the luminescence intensity at 25°C; the quantum efficiency of the cyan nitrogen oxide fluorescent material that can be excited by purple light under purple light excitation is greater than 80%, so that the fluorescent material is applied to white light LED devices.

[0102] Example 6

[0103] The raw material is BaCO 3 、Eu 2 O 3 , Y 2 O 3 and Si 3 N 4 , BaCO 3 、Eu 2 O 3 , Y 2 O 3 and Si 3 N 4 The molar ratio of Ba, Eu, Y and Si in the sample is 1.9:0.1:4:1. The raw materials are ground and mixed, then put into a crucible and sintered at 1400℃ for 6h in a high temperature furnace under an ammonia atmosphere. The theoretical chemical composition is Ba 1.9 Eu 0.1 Y 4 SiO 7 N 2 of fluorescent materials.

[0104] The fluorescent material obtained in Example 6 was analyzed using a fluorescence spectrometer to obtain its emission and excitation spectra, as shown in FIG. Fig.12As shown. Under the excitation of 400nm purple light, the main peak of the emission spectrum of the material is located at 490nm, and the main peak of the corresponding excitation spectrum is located at 400nm. The quantum efficiency tester is used to test the quantum efficiency of the material corresponding to Example 6, and the quantum efficiency is 89.8%. The luminescence intensity of the material at different temperatures is measured using a luminescent material thermal quenching performance tester. It is found that the luminescence intensity of the material at 100℃ under the excitation of 400nm purple light is 0.93 times that at 25℃, as shown in FIG. Fig.13 As shown, see Table 1 for details. It can be seen that Example 6 is a cyan oxynitride fluorescent material that can be excited by violet light. Under the excitation of violet light of 400nm, the main peak of the emission spectrum of the cyan oxynitride fluorescent material is located between 485 and 500nm; the luminous intensity of the cyan oxynitride fluorescent material that can be excited by violet light at 100°C is 0.90 to 0.95 times the luminous intensity at 25°C; the quantum efficiency of the cyan oxynitride fluorescent material that can be excited by violet light under violet light excitation is greater than 80%, so that the fluorescent material is applied to white light LED devices.

[0105] Example 7

[0106] The raw material is BaCO 3 、Eu 2 O 3 , Y 2 O 3 and Si 3 N 4 , BaCO 3 、Eu 2 O 3 , Y 2 O 3 and Si 3 N 4 The molar ratio of Ba, Eu, Y and Si in the sample is 1.88:0.12:4:1. The raw materials are ground and mixed, then put into a crucible and sintered at 1400℃ for 6h in a high temperature furnace under an ammonia atmosphere. The theoretical chemical composition is Ba 1.88 Eu 0.12 Y 4 SiO 7 N 2 of fluorescent materials.

[0107] The fluorescent material obtained in Example 7 was analyzed by using a fluorescence spectrometer, and it was found that the main peak of the emission spectrum of the material under the excitation of 400nm purple light was located at 492nm; the quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Example 7, and the quantum efficiency was 82.3%; the luminous intensity of the material at different temperatures was measured using a luminescent material thermal quenching performance tester, and it was found that the luminous intensity of the material at 100°C under the excitation of 400nm purple light was 0.94 times the luminous intensity at 25°C, as shown in Table 1. It can be seen that Example 7 is a cyan nitrogen oxide fluorescent material that can be excited by purple light. Under the excitation of 400nm purple light, the main peak of the emission spectrum of the cyan nitrogen oxide fluorescent material is located between 485 and 500nm; the luminous intensity of the cyan nitrogen oxide fluorescent material that can be excited by purple light at 100°C is 0.90 to 0.95 times the luminous intensity at 25°C; the quantum efficiency of the cyan nitrogen oxide fluorescent material that can be excited by purple light under purple light excitation is greater than 80%, so that the fluorescent material is applied to white light LED devices.

[0108] Example 8

[0109] The raw material is BaCO 3 、Eu 2 O 3 , Y 2 O 3 and Si 3 N 4 , BaCO 3 、Eu 2 O 3 , Y 2 O 3 and Si 3 N 4 The molar ratio of Ba, Eu, Y and Si in the sample is 1.85:0.15:4:1. The raw materials are ground and mixed, then put into a crucible and sintered at 1400℃ for 6h in a high temperature furnace under an ammonia atmosphere. The theoretical chemical composition is Ba 1.85 Eu 0.15 Y 4 SiO 7 N 2 of fluorescent materials.

[0110] The fluorescent material obtained in Example 8 was analyzed by using a fluorescence spectrometer, and it was found that the main peak of the emission spectrum of the material under the excitation of 400nm purple light was located at 495nm; the quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Example 8, and the quantum efficiency was 85.72%; the luminescence intensity of the material at different temperatures was measured using a luminescent material thermal quenching performance tester, and it was found that the luminescence intensity of the material under the excitation of 400nm purple light at 100°C was 0.92 times the luminescence intensity at 25°C, as shown in Table 1. It can be seen that Example 8 is a cyan nitrogen oxide fluorescent material that can be excited by purple light. Under the excitation of 400nm purple light, the main peak of the emission spectrum of the cyan nitrogen oxide fluorescent material is located between 485 and 500nm; the luminescence intensity of the cyan nitrogen oxide fluorescent material that can be excited by purple light at 100°C is 0.90 to 0.95 times the luminescence intensity at 25°C; the quantum efficiency of the cyan nitrogen oxide fluorescent material that can be excited by purple light under purple light excitation is greater than 80%, so that the fluorescent material is applied to white light LED devices.

[0111] Example 9

[0112] The raw material is BaCO 3 、Eu 2 O 3 , Y 2 O 3 and Si 3 N 4 , BaCO 3 、Eu 2 O 3 , Y 2 O 3 and Si 3 N 4 The molar ratio of Ba, Eu, Y and Si in the sample is 1.82:0.18:4:1. The raw materials are ground and mixed, then put into a crucible and sintered at 1400℃ for 6h in a high temperature furnace under an ammonia atmosphere. The theoretical chemical composition is Ba 1.82 Eu 0.18 Y 4 SiO 7 N 2 of fluorescent materials.

[0113] The fluorescent material obtained in Example 9 was analyzed by a fluorescence spectrometer, and it was found that the main peak of the emission spectrum of the material under the excitation of 400nm purple light was located at 498nm; the quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Example 9, and the quantum efficiency was 86.1%; the luminescence intensity of the material at different temperatures was measured by a luminescent material thermal quenching performance tester, and it was found that the luminescence intensity of the material at 100°C under the excitation of 400nm purple light was 0.92 times that at 25°C, as shown in Table 1. It can be seen that Example 9 is a cyan nitrogen oxide fluorescent material that can be excited by purple light. Under the excitation of 400nm purple light, the main peak of the emission spectrum of the cyan nitrogen oxide fluorescent material is located between 485 and 500nm; the luminescence intensity of the cyan nitrogen oxide fluorescent material that can be excited by purple light at 100°C is 0.90 to 0.95 times that at 25°C; the quantum efficiency of the cyan nitrogen oxide fluorescent material that can be excited by purple light under purple light excitation is greater than 80%, so that the fluorescent material is applied to white light LED devices.

[0114] Example 10

[0115] The raw material is BaCO 3 、Eu 2 O 3 , Y 2 O 3 and Si 3 N 4 , BaCO 3 、Eu 2 O 3 , Y 2 O 3 and Si 3 N 4 The molar ratio of Ba, Eu, Y and Si in the sample is 1.8:0.2:4:1. The raw materials are ground and mixed, then put into a crucible and sintered at 1400℃ for 6h in a high temperature furnace under an ammonia atmosphere. The theoretical chemical composition is Ba 1.8 Eu 0.2 Y 4 SiO 7 N 2 of fluorescent materials.

[0116] The fluorescent material obtained in Example 10 was analyzed by a fluorescence spectrometer, and it was found that the main peak of the emission spectrum of the material under the excitation of 400nm purple light was located at 500nm; the quantum efficiency tester was used to test the quantum efficiency of the material corresponding to Example 10, and the quantum efficiency was 81.9%; the luminescence intensity of the material at different temperatures was measured by a luminescent material thermal quenching performance tester, and it was found that the luminescence intensity of the material at 100°C under the excitation of 400nm purple light was 0.90 times the luminescence intensity at 25°C, as shown in Table 1. It can be seen that Example 10 is a cyan nitrogen oxide fluorescent material that can be excited by purple light. Under the excitation of 400nm purple light, the main peak of the emission spectrum of the cyan nitrogen oxide fluorescent material is located between 485 and 500nm; the luminescence intensity of the cyan nitrogen oxide fluorescent material that can be excited by purple light at 100°C is 0.90 to 0.95 times the luminescence intensity at 25°C; the quantum efficiency of the cyan nitrogen oxide fluorescent material that can be excited by purple light under purple light excitation is greater than 80%, so that the fluorescent material is applied to white light LED devices.

[0117] Table 1 Luminescence properties of materials corresponding to comparative examples and examples

[0118]

[0119] Embodiment 11

[0120] The blue fluorescent material (BaMgAl 10 O 17 :Eu), cyan oxynitride fluorescent material (Ba 1.9 Eu 0.1 Y 4 SiO 7 N 2 )、Green fluorescent material (β-sialon:Eu), Yellow fluorescent material (Y 3 Al 5 O 12 :Ce) and red fluorescent material (CaAlSiN 3 :Eu) and epoxy resin are mixed evenly in a mass ratio of 1:0.56:0.85:1:1.2:6, and the mixture is coated on a purple LED with a main peak of emission spectrum at 400nm, encapsulated, and then cured at 150℃ for 2h to obtain a white light LED light source with a color rendering index of 96.8. The spectrum of the obtained LED light source is tested using an LED spectrum tester, and its spectral distribution is as follows Fig.14 As shown, it can be seen that the continuity of the spectrum is good.

[0121] The above embodiments are only used to illustrate the implementation methods of the present invention and to explain the technical features of the present invention, and are not used to limit the protection scope of the present invention. Any changes or equivalent arrangements that can be easily completed by a person familiar with this technology belong to the scope claimed by the present invention, and the scope of protection of the present invention shall be subject to the claims.

Claims

1. A cyan nitride oxide fluorescent material that can be excited by purple light, characterized in that: The chemical formula of the cyan nitrogen oxide fluorescent material that can be excited by purple light is: Ba 2-x Eu x Y4SiO7N2, wherein 0.05≤x≤0.2; under violet light excitation, the main peak of the emission spectrum of the cyan nitride fluorescent material that can be excited by violet light is located between 485 and 500 nm; the crystal structure of the corresponding matrix of the cyan nitride fluorescent material that can be excited by violet light belongs to the tetragonal crystal system, and the space group is P4; the luminous intensity of the cyan nitride fluorescent material that can be excited by violet light at 100°C is 0.90 to 0.95 times the luminous intensity at 25°C; the quantum efficiency of the cyan nitride fluorescent material that can be excited by violet light under violet light excitation is greater than 80%.

2. The cyan oxynitride fluorescent material that can be excited by violet light as claimed in claim 1, characterized in that: The x is 0.

1.

3. The method for preparing a cyan oxynitride fluorescent material that can be excited by violet light according to any one of claims 1 to 2, characterized in that: A Ba precursor, a Eu precursor, a Y precursor and a Si precursor are mixed, and a high-temperature solid-phase reaction is carried out in an ammonia atmosphere to obtain a cyan nitrogen oxide fluorescent material that can be excited by purple light; wherein the Si precursor is selected from Si3N4.

4. The method for preparing a cyan nitrogen oxide fluorescent material that can be excited by purple light as claimed in claim 3, characterized in that: The molar ratio of Ba, Eu, Y and Si in the Ba precursor, Eu precursor, Y precursor and Si precursor is (2-x):x:4:1, wherein 0.05≤x≤0.

2.

5. The method for preparing a cyan nitrogen oxide fluorescent material that can be excited by purple light as claimed in claim 3, characterized in that: The purity of the Ba precursor, Eu precursor, Y precursor and Si precursor is not less than 99.5%.

6. The method for preparing a cyan oxynitride fluorescent material that can be excited by violet light as claimed in claim 3, characterized in that: The temperature of the high temperature solid phase reaction is 1350-1450° C., and the time of the high temperature solid phase reaction is 4-10 hours.

7. The method for preparing a cyan nitrogen oxide fluorescent material that can be excited by purple light as claimed in claim 3, characterized in that: The Ba precursor is selected from one or more of Ba carbonate, Ba oxide, Ba oxalate and Ba nitrate; the Eu precursor is selected from one or more of Eu carbonate, Eu oxide, Eu oxalate and Eu nitrate; the Y precursor is selected from one or more of Y carbonate, Y oxide, Y oxalate and Y nitrate.

8. A white light LED light source, characterized in that: It comprises a cyan nitride fluorescent material that can be excited by violet light as described in any one of claims 1 to 2, or a cyan nitride fluorescent material that can be excited by violet light obtained by the preparation method of any one of claims 3 to 7.

9. A white light LED light source as claimed in claim 8, characterized in that: It also includes an LED chip with an emission wavelength between 380 and 420 nm.

Citation Information

Patent Citations

  • Multi-component oxynitride or nitride base fluorescent powder and preparation method thereof

    CN101629077A

  • Fluorescent powder for field emission and method for preparing same

    CN101717638A

  • Cyan luminescent material and preparation method thereof

    CN102899039A

  • A cyan fluorescent material and its preparation method

    CN106928259B

  • An LED light source and lamp with a partial spectral structure of daylight visible light

    CN107565006B